Effect of water quality regimes, irrigation schedules, RSC levels and neutralizer on physiological and biochemical behaviour of fodder sorghum (Sorghum bicolor) - Soni, Pooja Gupta; Yadav, R K; Kumar, Ashwani; Kumar, Rakesh; Gajender, Gajender; Yadav, Taramani; Sharma, Arpita; Kushwaha, Manish (The Indian Journal of Agricultural Sciences, 2020)
Two independent experiments were carried out to study the physio-biochemical responses of fodder sorghum (Sorghum bicolor L.) under different irrigation water quality, irrigation schedules, RSC levels and neutralizer. Both these experiments were conducted during kharif season of 2013 in micro-plots of CSSRI, Karnal. First experiment was designed to evaluate the effect of different water quality irrigations scheduled at varying ID/CPE ratios. This experiment was laid out in factorial randomised block design (RBD) with four replications, consisting of nine treatment combinations of three irrigation water quality levels [Tube well water, cyclic use of Tube well water : Sewage water and Sewage water ] and three irrigation schedules based on ID/CPE ratios (0.8, 1.0 and 1.2). Second experiment was carried out to assess the effect of RSC levels in irrigation water and their neutralization with gypsum and H2SO4. This experiment was conducted in randomised block design with four replications, consisted of five treatments of different RSC levels [control (No RSC), RSC – 5 meq l-1, RSC–10 meq l-1, RSC – 10 meq l-1 (neutralized with gypsum), RSC – 10 meq l-1 (neutralized with H2SO4)]. In first experiment, The sewage water recorded 19.18 and 11.73% higher chlorophyll a and total soluble protein at first cut and 9.56 and 11.92% at second cut compared to TW. The 1.2 ID/ CPE ratio increased the chlorophyll a (26.5 and 16.5 % ) and total soluble protein (22.9 and 25.4 %) compared to 0.8 ID/CPE ratio, at first and second cut, respectively. In second experiment, chlorophyll a and b was adversely affected with the application of RSC 10 meq l-1 water with the maximum reduction by 17.71% at 1st cut and 19.62% at 2nd cut in case of chlorophyll a and 41.94% at 1st cut and 39.98% at 2nd cut for chlorophyll b compared to control (No RSC). Our results concluded that sewage water irrigation scheduled at 1.2 ID/CPE ratio proved superior and thus it may be adapted as a choice for getting higher green fodder yield with better physiological responses. From second experiment, it was inferred that higher RSC of irrigation water negatively affected the performance of fodder sorghum. It should be neutralized either by gypsum or sulphuric acid for obtaining better physiology as well as for fodder yield.